Persistent Diffusion Abnormalities in the Brain Stem of Three Children with Mitochondrial Diseases - Sakai, Y.; Kira, R.; Torisu, H.; Ihara, K.; Yoshiura, T.; Hara, T. (American Journal of Neuroradiology, 2006)
SUMMARY: We report 2 children (patients 1 and 2) with Kearns-Sayre syndrome and 1 (patient 3) with Leigh syndrome, who underwent serial diffusion-weighted MR imaging (DWI) studies for 2.8 (patient 1), 4.2 (patient 2), and 1.0 years (patient 3). The DWI revealed the persistent hyperintense signals in the pontine and mesencephalic tegmenta. The apparent diffusion coefficient in the affected regions remained constantly low, suggesting that cytotoxic edema and spongiform degenerations may compose these brain stem lesions.